Towards recycling of ionic liquids in fiber spinning process - Carbohydrate transformation products in aqueous ionic liquid solutions studied by liquid chromatography/quadrupole time-of-flight mass spectrometry - Pitkänen, Leena; Tuominen, Monika; Asadzadeh, Behnaz; Uusi-Kyyny, Petri; Kaipanen, Kalle; Kilpeläinen, Petri; Hummel, Michael; Sixta, Herbert (Elsevier, 2026)
New technologies for the production of man-made cellulose fibers are being developed to produce fibers sustainably for various textile applications. The Ioncell® process uses an ionic liquid in which cellulose is dissolved to form a spinning solution. This spinning solution is spun into an aqueous coagulation bath using dry-jet wet spinning technology to produce Ioncell fibres. In order to develop a sustainable and economically viable process, the ionic liquid must be efficiently recycled in the process. Organic compounds resulting from degradation reactions of the cellulosic materials used for fiber production might accumulate in the ionic liquid over time and reduce its dissolution power. This study aimed to tentatively identify the main carbohydrate transformation products from aqueous ionic liquid solution. In addition to the actual coagulation bath sample, carbohydrate transformation reactions were studied using model samples. The main monomeric carbohydrate constituents of a hardwood pulp, glucose and xylose, were mixed with an ionic liquid and water and heated to 90 °C for 8 h to accelerate the transformation reactions. Most of the original monosaccharides were converted into other compounds, so that after the heat treatment only 11 wt% of the glucose and 1.1 wt% of the xylose remained. The liquid chromatography/time-of-flight mass spectrometry analyses revealed that both the spin bath sample and model samples contained mainly hydroxycarboxylic acids and carboxylic acids. The superbase of ionic liquid catalyzed the alkaline transformation reactions of carbohydrates.
Keywords: carbohydrates; organic acids; oxidation; separations; ionic liquid; LC-qTOF-MS